2008
DOI: 10.1177/0363546508314721
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Reconstruction of the Anterior Cruciate Ligament Using Bone-Patellar Tendon-Bone Autograft

Abstract: Mean follow-up was 11.6 +/- 0.8 years. Nine graft ruptures occurred. The satisfaction rate was excellent (90%). Seventy patients (74%) were still actively participating in sports. The mean subjective IKDC 2000 score was 90.5 +/- 8.8 points. The IKDC score was statistically correlated to laxity, time from injury, and osteoarthritis development at final follow-up. Ninety-one percent of patients were graded A or B according to the overall IKDC score. The radiological assessment reported osteoarthritis development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
5
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(147 citation statements)
references
References 33 publications
6
134
5
2
Order By: Relevance
“…This study intended to identify factors associated with our long-term outcomes, focussing in particular on long-term knee-joint stability and prevalence of knee OA. It was also based on a homogenous sample, a standardised operative procedure and postoperative rehabilitation, and a short interval from injury to ACL reconstruction of only two to three weeks [3,4,13,20]. Furthermore, it only focussed on isolated ACL injuries.…”
Section: Discussionmentioning
confidence: 99%
“…This study intended to identify factors associated with our long-term outcomes, focussing in particular on long-term knee-joint stability and prevalence of knee OA. It was also based on a homogenous sample, a standardised operative procedure and postoperative rehabilitation, and a short interval from injury to ACL reconstruction of only two to three weeks [3,4,13,20]. Furthermore, it only focussed on isolated ACL injuries.…”
Section: Discussionmentioning
confidence: 99%
“…23 This trend is believed to be related to improved fixation techniques and the perception that hamstring grafts are associated with less morbidity than patellar ligament grafts. 10,11,14,21,22 Several in vitro kinematic investigations demonstrated that single-bundle reconstructions alone were insufficient in controlling the combined rotatory load and valgus torque that simulates the pivot shift test [stability paper 9,22,27]. Single bundle ACL reconstruction using tendon grafts has shown to have good results by many investigators.…”
Section: Discussionmentioning
confidence: 99%
“…5 The BPTB autograft has given excellent clinical results and high level of patient satisfaction after a long term follow-up. 6,9 In vitro studies have been proven hamstring grafts to be as strong as the original ACL. 10 But some authors have reported inferior stability in vivo compared to BTB grafts.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, only 50% of all individuals who sustain an ACL injury will develop PTOA. 6 Thus, other factors may be more important in joint degeneration, including meniscal status [29][30][31][32][33] and articular cartilage damage sustained at the time of injury. 3 Future investigations are necessary to determine the precise contributors to PTOA development.…”
Section: Discussionmentioning
confidence: 99%